Effects of carbon dioxide narcosis on ovary activation and gene expression in worker honeybees, Apis mellifera - Koywiwattrakul, Preeyada (University of Arizona Library, 2005)
In an effort to uncover genes associated with ovary activation in honey bee workers, the extent to which eight candidate genes co-varied in their expression with experimentally-induced changes in worker reproductive state was examined. Groups of caged, queenless workers narcotized with CO(2) on consecutive days early in adult life showed a significantly lower level of ovary activation than did groups of untreated workers. This same experimental treatment, by contrast, is known to accelerate ovary activation and induce egg laying in virgin honey bee queens – an observation that suggests that CO(2) narcosis has contrasting effects in queen versus worker ovary activation. Experimentally-induced changes to worker reproductive state were associated with changes in gene expression. Vitellogenin, an egg yolk precursor, and transferrin, an iron transporter, were two transcripts found to be significantly down-regulated as a function of the ovary-inhibiting treatment. CO(2) narcosis did not effect the expression of six other genes selected as putative markers for processes that may underlie ovary activation. The show that the expression of vitellogenin and transferrin is correlated with ovary activation in workers, and may therefore be part of the gene network involved in the regulatory control of functional sterility in honeybees.